MEDIA PEMBELAJARAN BERBASIS SCRATCH: PENGEMBANGAN GAME EDUKATIF JELITA UNTUK OPTIMALISASI HASIL BELAJAR IPAS DI SEKOLAH DASAR - Rahmadina, Ahliza Azahra; Akhmad Junaedi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Technological advances can certainly help teachers in creating appropriate learning media so that they can support the achievement of learning objectives. However, many teachers still do not take advantage of this convenience, limited materials in schools are also one of the reasons that have an impact on low student learning outcomes in the subject of Social Sciences. The purpose of this study was to determine the effectiveness of the JELITA game media on the learning outcomes of grade IV Social Sciences at SDN Tlogomulyo. The type of research used in this study is Research and Development with the ADDIE model. There are two methods in data collection, through test techniques (pretest and posttest) and non-test (observation, interviews, questionnaires, and documentation). Data analysis techniques are presented in quantitative and qualitative forms. This study uses product analysis, initial data analysis, and final data analysis. The JELITA game media developed in this study received a feasibility test result from material experts of 91% (very feasible), and the media feasibility test assessment reached 75% (feasible). The Dependent T-Test obtained a significance result of 0.000 which indicated a significant increase, while the N-gain test result reached 0.6184 which was included in the moderate increase criteria. From these results, it can be concluded that the JELITA game learning media has been successfully developed including in the effective and feasible category in improving the learning outcomes of grade IV students of SDN Tlogomulyo. The following is a paraphrase that is appropriate for writing an article, with the meaning and logical structure of the argument maintained. These findings show the importance for teachers and educational institutions to implement innovative learning methods by integrating technology, as a response to the challenges of education in the modern era.